Penggunaan Aplikasi TikTok pada Kalangan Remaja saat Pandemi Covid-19 di Kota Denpasar - Naidi, Martha Fransiska; Sastri Mahadewi, Ni Made Anggita; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
TikTok application is one of the social media platforms for uploading videos or content. TikTok allows users to create short videos with various effects and music so that the content can become more interesting and creative. The use of the TikTok application has positive and negative impacts on its use which causes changes in the behavior of TikTok users themselves. The formulation of the problem in this study is how the form of using the TikTok application among adolescents during the co-19 pandemic and how the behavioral impact on the use of the TikTok application. This research uses descriptive qualitative research. The results show that the form and impact of using the TikTok application is contextual and depends on how individuals use it. If used wisely, TikTok can be a powerful tool for entertainment, creativity, learning and promotion. However, misuse and irresponsible use can have a negative impact on the well-being of individuals and society in general. Based on Sven Windahl's uses and effects theory, there is a relationship that the use and content of the TikTok application can have an effect and impact on its users.